Social constructions and the role of communication in shaping the life world of the PNP 2014 recruits - De Torres, Julia A. (College of Mass Communication, University of the Philippines Diliman, 2015)
"Communication constructs life worlds or social worlds as people interact with one another. This dissertation describes and analyzes the social constructions and the role of communication in the formation of the life worlds of the 2014 PNP recruits. Using a dominantly qualitative approach qualitative approach and supplemented by quantitative method, the study delved on the communication and interaction used before and during training by the participants. Narratology unlocked the social constructions of the informants and respondents in the study. Narratives enriched by signs and symbols became the medium for the social construction of the recruits' socio-cultural values, gender and place of origin. Rich data were from focus group discussions and key informant interviews alongside the conducted trainings centers in PNP centers in Luzon, Visayas, and Mindanao. A survey was also conducted in the three major islands, with respondents belonging to PNP Batch 2014. Understanding how a regimented environment affects the recruits' social construction and communication as well as the emergence of a subculture makes the PNP a challenging arena in which to conduct a research on these concepts and assumptions."